2015
DOI: 10.1007/s10147-015-0880-x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of preoperative butyrylcholinesterase as an independent predictor of biochemical recurrence-free survival in patients with prostate cancer treated with radical prostatectomy

Abstract: This study validated preoperative serum BChE levels as an independent prognostic factor for PCa after RP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 23 publications
2
18
1
Order By: Relevance
“…Patient demographics are shown in Table 3. Staging and grading information regarding the tumors and patient follow-up have been described previously [35]. In brief, PSA recurrence after RP was defined by two consecutive PSA values of >0.2 ng/mL with a 1-month interval and after a postoperative decrease below the detection limit (<0.001 ng/mL).…”
Section: Methodsmentioning
confidence: 99%
“…Patient demographics are shown in Table 3. Staging and grading information regarding the tumors and patient follow-up have been described previously [35]. In brief, PSA recurrence after RP was defined by two consecutive PSA values of >0.2 ng/mL with a 1-month interval and after a postoperative decrease below the detection limit (<0.001 ng/mL).…”
Section: Methodsmentioning
confidence: 99%
“…Serum levels of BChE has been found to decrease during inflammation. Koie et al [54] in a retrospective study reviewed the pathological records of 535 PC patients submitted to RP. The cut-off point for the serum BChE level was determined as 168 IU/L according to previously described methods.…”
Section: Prognostic Value Of Inflammation In Prostate Cancer Submittementioning
confidence: 99%
“…As of now, the studies are mainly retrospective, but some findings may suggest that the grade of inflammation in preoperative biopsy specimens could be used to risk-stratify men with PC for risk of biochemical progression after RP [54, 55]. However, in a multivariate analysis after adjustment with the other clinical parameters (PSA, clinical stage, Gleason score), inflammation did not result an independent predictor.…”
Section: Prognostic Value Of Inflammation In Prostate Cancer Submittementioning
confidence: 99%
“…A study including 108 academic and community practices throughout Japan found that preoperative serum PSA levels and Gleason scores were higher in a Japanese cohort compared with those in an American cohort . Similarly, several previous reports of Japanese cohorts have reported poorer prognosis after RP compared with North American or European cohorts . It has been reported that the rate of PSA screening in Japan is much lower than that in European counties .…”
Section: Introductionmentioning
confidence: 96%